EFFECT OF PERSON ORGANIZATION FIT AND JOB SATISFACTION OF ORGANIZATION COMMITMENT WITH ORGANIZATIONAL CITIZENSHIP BEHAVIOR AS AN INTERVENING VARIABLE - Patricia Dhiana Paramita (Universitas Pandanaran, 2015)
PT. Meditama Bhakti Jaya Semarang experiencing problems in which the organization's commitment in the company is low, so the impact on the low organizational citizenship behavior. Presumably it is motivated by the low oganization person fit and employee satisfaction. The formulation of the problem in this research is how the management of PT. Meditama Bhakti Jaya Semarang increase organizational commitment positively impact organizational citizenship beavior.The population in this study were all employees who work in PT. Meditama Bhakti Jaya Semarang numbering 70 people. The sampling technique using census method. Analysis of data using multiple linear regression 2, goodness of fit and path analysis. Based on the analysis, it is known that the person organization fit and job satisfaction and significant positive effect on organizational commitment either partially or simultaneously. Organizational commitment and significant positive effect on organizational citizenship behavior and mediates the effect of person organization fit and job satisfaction of employees.Keywords: person organization fit, job satisfaction, organizational commitment and organizational citizenship behavior